"For the tyrant shall be no more": Reflections on and lessons from "The Arab Spring" in North Africa, the Middle East and the Civil Rights and anti-apartheid struggles - Boesak, Allan (HTS teologiese studies, 2011)
The revolutionary events sweeping North Africa and the Middle East, called the ‘Arab Spring’, are of great historic significance. They challenge not only political and social realities in those countries; they confront us, the spectators to these momentous events with serious questions about our own political, cultural and theological perceptions, concepts and prejudices. This article probes, from a Black Liberation theology point of view, these events at several levels: (1) what are the connections between the ‘Arab Spring’ and the two other historic movements for social change, the Civil Rights struggle in the United States of America, and the antiapartheid struggle in South Africa; (2) what lessons are to be learnt from these events?; (3) the article revisits the question of M.M. Thomas, in terms of whether God is at work in events of social upheaval and revolutionary change, and if so, ‘how?’; and (4) what is the meaning and consequences of international, and more importantly, inter-religious solidarity with the people of those regions? The article discusses the meaning, complexity and efficacy of nonviolence and choices for violence or nonviolence in such situations of conflict and the questions these raise for theological reflection, prophetic action and Christian integrity.